Towards non-blind optical tweezing by finding 3D refractive index changes through off-focus interferometric tracking - Benjamin Landenberger (Nature Portfolio, 2021)
Optical manipulation of large objects is challenging as optical trap positions are blindly chosen. Here, the authors present off-focus interferometric tracking, which localises optimal grabbing positions with increased refractive index, by analysing the beam deformations of several holographic optical traps.